Environmental Toxicology and Risk Assessment: Modeling and Risk Assessment Sixth Volume 1997
DOI: 10.1520/stp12251s
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results Using the Early Embryo Teratogenesis Assay: A Comparison of Early Embryo Abnormalities with Late Embryo and Hatchling Teratogenic Changes

Abstract: Classical evaluations of the effects of toxicants on development in birds for ecological impact assessments and teratogenic evaluation generally entail an evaluation of the late embryo, immediately before hatching, or young hatchling. In the laboratory, these studies generally require approximately three weeks before one can evaluate the late embryo or hatchling, and a full teratogenic evaluation of growth and developmental parameters is relatively time intensive. Recent studies have shown that many teratogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Later studies evaluating the effects of TCDD and PCBs on the development of embryonic hearts documented that the dose-responsive TCDD/PCB-induced heart abnormalities, like the brain abnormalities, are quantifiably detectable very early in embryonic development (Henshel et al, 1993). These characteristic heart abnormalities have been observed in tree swallow embryos from Winston-Thomas in a related part of our study (Henshel et al, 1997). Walker et al (1997) and Walker and Catron (2000) confirmed that approximately 60 ng/g TCDD toxic equivalents (TEQs) caused edema, structural changes, and increased heart weight due to dilation in developing chicken hearts by embryonic day 10 or 12.…”
Section: Pcb-correlated Effects On Passerine Organ Si 13supporting
confidence: 69%
“…Later studies evaluating the effects of TCDD and PCBs on the development of embryonic hearts documented that the dose-responsive TCDD/PCB-induced heart abnormalities, like the brain abnormalities, are quantifiably detectable very early in embryonic development (Henshel et al, 1993). These characteristic heart abnormalities have been observed in tree swallow embryos from Winston-Thomas in a related part of our study (Henshel et al, 1997). Walker et al (1997) and Walker and Catron (2000) confirmed that approximately 60 ng/g TCDD toxic equivalents (TEQs) caused edema, structural changes, and increased heart weight due to dilation in developing chicken hearts by embryonic day 10 or 12.…”
Section: Pcb-correlated Effects On Passerine Organ Si 13supporting
confidence: 69%
“…Other studies evaluating the developmental effects of TCDD and PCBs on hearts have demonstrated that teratogenic changes are detectable as soon as the heart starts to form during embryonic development. Henshel [4,22] as well as Henshel et al [23] and Dickerson et al [37] showed that initial heart development was affected adversely by TCDD and that these delays and early heart malformations were observable at 2 and 10 pg TCDD/g egg (ϳ0.1 and 0.5 ng/egg), the lowest doses tested in each study. Walker et al [38] examined hearts from 10-d-old chicken embryos exposed to 1 pM TCDD per egg (0.54 ng of TCDD per 60-g egg; 9 ppt) from embryonic day 0 to embryonic day 10.…”
Section: Discussionmentioning
confidence: 92%
“…The heart is susceptible to dioxin and dioxin-like chemical exposure [6][7][8][22][23][24][25][26][27][28][29]. Previous work by our laboratory demonstrated that developmental TCDD exposure increased the incidence and severity of teratogenic heart deformities in chicken embryos [7,[22][23][24] exposed throughout the incubation period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation